1983
DOI: 10.1172/jci110799
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hyperglycemia Reduces Surface Active Material Flux in Tracheal Fluid of Fetal Lambs

Abstract: A B S T R A C T I tested the hypothesis that chronic hyperglycemia alters fetal lung maturation by continuous infusion of glucose (14±2 mg/kg per min, mean±SE) from 112 up to 145 d gestation into six chronically catheterized fetal lambs from which tracheal fluid could be collected. Serum glucose levels (32±2 mg/dl) and serum insulin levels (38±4 ,uU/ml) in these glucose-treated fetuses were significantly higher than serum glucose levels (18±2 mg/dl, P <0.001) and serum insulin levels (12±3 IAU/ml, P < 0.001) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In situations where glucose delivery to the lung remains high near term, metabolic maturation of the fetal lung may be compromised. This is supported by the observation that fetal hyperglycemia is implicated as a major etiologic factor in the pathogenesis of the respiratory distress syndrome (leading to decreased surfactant availability) in the infants of diabetic mothers (24,25). Further, in vitro studies have described a much greater lung utilization of glucose in fetal animals than in newborn and older animals (26).…”
Section: Discussionmentioning
confidence: 86%
“…In situations where glucose delivery to the lung remains high near term, metabolic maturation of the fetal lung may be compromised. This is supported by the observation that fetal hyperglycemia is implicated as a major etiologic factor in the pathogenesis of the respiratory distress syndrome (leading to decreased surfactant availability) in the infants of diabetic mothers (24,25). Further, in vitro studies have described a much greater lung utilization of glucose in fetal animals than in newborn and older animals (26).…”
Section: Discussionmentioning
confidence: 86%
“…Warburton (10,11) has reported that both primary hyperinsulinemia with concomitant hypoglycemia, and chronic hyperglycemia with secondary hyperinsulinemia reduce SAM flux into tracheal fluid of fetal lambs. Before 128 d gestation, SAM flux into tracheal fluid in the current experiment was similar to Warburton's previously reported data.…”
Section: Discussionmentioning
confidence: 99%
“…However, the insulin-treated fetal lambs in this study became hypoglycemic relative to controls. In a subsequent study, Warburton (11) reported that chronic hyperglycemia with secondary hyperinsulinemia also reduces SAM flux into tracheal fluid of fetal lambs. In the human fetus, maternal diabetes mellitus leads to fetal hyperglycemia and hyperinsulinemia.…”
Section: Introductionmentioning
confidence: 93%
“…Ewes were operated on at 110 days gestation under epidural anesthesia with 0.5% Pontocaine as described previously (3,5).…”
Section: Methodsmentioning
confidence: 99%